Pain neurosurgery - Sagher, Oren; Levin, Emily; Pilitsis, Julie G. ([New York] : Oxford University Press, 2019)
Part of the'Neurosurgery by Example' series, this volume on pain neurosurgery presents exemplary cases in which renowned authors guide readers through the assessment and planning, decision making, surgical procedure, after care, and complication management of common and uncommon disorders. Containing a focused review of medical evidence and expected outcomes,'Pain Neurosurgery' is appropriate for neurosurgeons who wish to learn more about a subspecialty, and those preparing for the American Board of Neurological Surgery oral examination.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 19, 2019).
Keywords: Pain medicine; Pain -- Treatment; Pain -- Surgery; Nervous system -- Surgery